Genome Sequencing Reveals a Mixed Picture of SARS-CoV-2 Variant of Concern Circulation in Eastern Uttar Pradesh, India - Deval, Hirawati; Nyayanit, Dimpal A.; Mishra, Shailendra Kumar; Yadav, Pragya D.; Zaman, Kamran; Shankar, Prem; Misra, Brij R.; Behera, Sthita Pragnya; Kumar, Niraj; Kumar, Abhinendra; Bhardwaj, Pooja; Dwivedi, Gaurav Raj; et al. (Frontiers in medicine, 2022)
Uttar Pradesh is the densely populated state of India and is the sixth highest COVID-19 affected state with 22,904 deaths recorded on November 12, 2021. Whole-genome sequencing (WGS) is being used as a potential approach to investigate genomic evolution of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus. In this study, a total of 87 SARS-CoV-2 genomes−49 genomes from the first wave (March 2020 to February 2021) and 38 genomes from the second wave (March 2021 to July 2021) from Eastern Uttar Pradesh (E-UP) were sequenced and analyzed to understand its evolutionary pattern and variants against publicaly available sequences. The complete genome analysis of SARS-CoV-2 during the first wave in E-UP largely reported transmission of G, GR, and GH clades with specific mutations. In contrast, variants of concerns (VOCs) such as Delta (71.0%) followed by Delta AY.1 (21.05%) and Kappa (7.9%) lineages belong to G clade with prominent signature amino acids were introduced in the second wave. Signature substitution at positions S:L452R, S:P681R, and S:D614G were commonly detected in the Delta, Delta AY.1, and Kappa variants whereas S:T19R and S:T478K were confined to Delta and Delta AY.1 variants only. Vaccine breakthrough infections showed unique mutational changes at position S:D574Y in the case of the Delta variant, whereas position S:T95 was conserved among Kappa variants compared to the Wuhan isolate. During the transition from the first to second waves, a shift in the predominant clade from GH to G clade was observed. The identified spike protein mutations in the SARS-CoV-2 genome could be used as the potential target for vaccine and drug development to combat the effects of the COVID-19 disease.